. .

 | 
 

 

         





: 60
: 26
: 2886
: 23/01/2009

:     28 2009 - 18:02


- :
-
-
-
-
2/ :
-
-
3/
4/ x
    





: 127
: 26
: 3064
: 25/10/2008

: :     28 2009 - 19:36



x+x
2x+1



lnu(x) ln ln
    





: 60
: 26
: 2886
: 23/01/2009

: :     29 2009 - 14:06

2 60
    
hiba




: 431
: 38
** : 4
: 3340
: 01/02/2008

: :     29 2009 - 15:39

(f+g)' = f' + g'
(f.g)' = f'.g+ g'.f
(1/f)' = -f'/f2
(f/g)' = (f'.g-g'.f)/g2
(ln f)= f'/f
(racine f) = f'/2racine f
F f(-x) = - f(x)
F f(-x) = f(x)
    





: 60
: 26
: 2886
: 23/01/2009

: :     5 2009 - 13:29

    





: 127
: 26
: 3064
: 25/10/2008

: :     5 2009 - 15:09



    
 
          
1 1

:
 ::   ::  -